An Innovative Framework of 5D BIM Solutions for Construction Cost Management: A Systematic Review - Vigneault, M.A.; Boton, C.; Chong, Heap-Yih (John); Cooper-Cooke, Barry (2019)
© 2019, CIMNE, Barcelona, Spain.